Enhanced photothermal therapy for tumor ablation: structural and functional insights into Bi2Se3 nanosheets as Light-to-Heat converter - Ming-Chung Wu; Yin-Hsuan Chang; Ting-Han Lin; Chun-Yuan Wu; Jia-Mao Chang; Yu-Jen Lu (Discover Nano)
Abstract Photothermal therapy (PTT) represents a promising advance in oncological treatments, utilizing light-induced heat mediated by photothermal agents to target and destroy cancer cells with high precision. Despite its potential, the clinical application of PTT is often limited by the efficiency of photothermal agents and their biocompatibility, highlighting a crucial need for novel materials that can safely and effectively convert light into therapeutic heat. This study demonstrates the two-dimensional Bi2Se3 nanosheets with tailored nanostructure via a solvothermal process. This study controls over their structural and photothermal properties by accurately optimizing synthesis conditions. In situ experiments provide insights into the crystallographic and phonon characteristics at varying temperatures, underscoring the thermal stability of Bi2Se3 nanosheets. Notably, these nanosheets demonstrate a high photothermal conversion efficiency, rapidly raising the tumor site temperature to 53.1 °C within 180 s, resulting in rapid tumor cell ablation. Significant tumor growth suppression is also observed, with the median survival of mice treated with the particle and light combination extending to 34 days. These findings confirm the stable in vivo thermal properties of Bi2Se3 nanosheets, establishing them as a potent candidate for future photothermal therapy applications.